The partimenti of Giovanni Paisiello : pedagogy and practice - Paraschivescu, Nicoleta (Eastman studies in music, 2022)
"Giovanni Paisiello (1740-1816) was one of the most important composers of opera in the eighteenth century. His operas were performed throughout Europe, and his fame led to appointments as a maestro di cappella and composer at prominent European courts. This book is the first study to address his work as a teacher of composition and what we would today call music theory. The practice of partimento (figured or unfigured bass lines) was an integral part of the training of musicians at the renowned conservatories in eighteenth-century Naples. By employing these often-unprepossessing partimento bass lines, young musicians learned the techniques of variation, improvisation, and composition while seated at the harpsichord. Paisiello's Regole per bene accompagnare il Partimento (Rules for Harpsichordists; 1782) survives in both autograph and printed forms. It contains forty-six partimenti that have long been considered the core of his pedagogic oeuvre. However, two recently discovered manuscripts contain a further forty-one unknown partimenti, notated as two- and three-part disposizioni (realizations). The present study offers numerous insights gleaned from the surviving sources and bolsters our understanding of how to perform the music of Paisiello and his contemporaries: music that has often survived in an incomplete form. These findings are relevant not just for keyboard players but also for singers, instrumentalists, and anyone interested in the inner workings of eighteenth- and early nineteenth-century music"--